Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Bawang Merah di Kabupaten Aceh Tamiang - Nurul Azizah; Lukman Hakim; Irwan A. Kadir (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Shallots are horticultural plants belonging to the spice vegetable group that have high economic value. The existence of shallot commodity cultivation is expected to increase income and improve welfare. But on the other hand there are several problems that occur to shallot farmers where the income of farmers does not always increase this is because there are several factors that affect the size of an income. The purpose of this study is to find out how much income farmers get from shallot farming and to determine the effect of production costs, total production, selling price and labor on the income of shallot farmers in Aceh Tamiang District. The sampling technique used is saturated sampling (census) totaling 58 farmers. This study uses analytical methods, namely income analysis and multiple linear regression analysis. The results showed that the average total revenue (TR) was Rp 42.288.793/farmer/mt or Rp 316.892.765/ha/mt and the average total cost (TC) was Rp 7.185.790/farmer/mt or Rp 53.847.005/ha/mt so that the average income of shallot farming is Rp 35.103.003/farmer/mt or Rp 263.045.760/ha/mt. Based on the results of multiple linear regression analysis the value of sig α (0,000 0,05) so that production costs (X1), total production (X2) , selling price (X3) and labor (X4) simultaneously have a significant effect on the income of shallot farmers in Aceh Tamiang District. While partially the production cost (X1), total production (X2) and selling price (X3) have a significant effect on the income of shallot farmers in Aceh Tamiang District, while on the labor variable (X4) the value of sig (0,718 0,05) so that labor has a positive and insignificant effect on the income of shallot farmers in Aceh Tamiang District.